2018
DOI: 10.1021/acs.jced.7b01015
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of the Na+, NH4+//SO42–, NO3–H2O Quaternary System at 303.15 and 323.15 K

Abstract: The equilibrium solubility of the quaternary system Na + , NH 4 + //SO 4 2−, NO 3 − −H 2 O at 303.15 and 323.15 K was determined by an isothermal dissolution equilibrium method. The weighing bottle method and Abbe refractometer were adopted to measure the density and refractive index of the aqueous liquid phase. The solid-phase invariant points at equilibrium were confirmed by Xray diffractometry. The complete diagrams of equilibrium phase, water content vs J(NO 3 − ) 2 of this quaternary system at 303.15 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In known reports, the phase diagram of the ternary NH 4 Br–NaBr–H 2 O system at 298.15 K has only one invariant point and three crystallization regions . Sang et al reported the phase diagram of the ternary NaBr–Na 2 SO 4 –H 2 O system at 298.15 to 373.15 K and found that NaBr existed in the form of NaBr·2H 2 O at 298.15 to 323.15 K. When the temperature was between 348.15 and 373.15 K, NaBr·2H 2 O is converted to NaBr. Rivett and Zhang et al measured the phase equilibrium data of the quaternary Na 2 SO 4 –NaCl–(NH 4 ) 2 SO 4 –NH 4 Cl–H 2 O system at 273.15 to 373.15 K and found that the double salt appeared at 273.15 to 323.15 K, and the crystallization region of the double salt disappeared at 333.15 K. The ternary subsystems of this quaternary system (Na + , NH 4 + //SO 4 2– –H 2 O, Na + , NH 4 + //Br – –H 2 O, and Na + //Br – , SO 4 2– –H 2 O) have been reported at 298.15 and 323.15 K. ,, There are no reports on the ternary NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system and the quaternary Na 2 SO 4 –NaBr–NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system. In view of this, the phase equilibrium data of the quaternary Na 2 SO 4 –NaBr–NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system and its ternary NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system at 298.15 and 323.15 K were determined using the isothermal method.…”
Section: Introductionmentioning
confidence: 99%
“…In known reports, the phase diagram of the ternary NH 4 Br–NaBr–H 2 O system at 298.15 K has only one invariant point and three crystallization regions . Sang et al reported the phase diagram of the ternary NaBr–Na 2 SO 4 –H 2 O system at 298.15 to 373.15 K and found that NaBr existed in the form of NaBr·2H 2 O at 298.15 to 323.15 K. When the temperature was between 348.15 and 373.15 K, NaBr·2H 2 O is converted to NaBr. Rivett and Zhang et al measured the phase equilibrium data of the quaternary Na 2 SO 4 –NaCl–(NH 4 ) 2 SO 4 –NH 4 Cl–H 2 O system at 273.15 to 373.15 K and found that the double salt appeared at 273.15 to 323.15 K, and the crystallization region of the double salt disappeared at 333.15 K. The ternary subsystems of this quaternary system (Na + , NH 4 + //SO 4 2– –H 2 O, Na + , NH 4 + //Br – –H 2 O, and Na + //Br – , SO 4 2– –H 2 O) have been reported at 298.15 and 323.15 K. ,, There are no reports on the ternary NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system and the quaternary Na 2 SO 4 –NaBr–NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system. In view of this, the phase equilibrium data of the quaternary Na 2 SO 4 –NaBr–NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system and its ternary NH 4 Br–(NH 4 ) 2 SO 4 –H 2 O system at 298.15 and 323.15 K were determined using the isothermal method.…”
Section: Introductionmentioning
confidence: 99%